The Impact of Hypomania on Aerobic Capacity and Cardiopulmonary Functioning—A Case Report - Shoval, Aura; Armstrong, Hilary F.; Vakhrusheva, Julia; Ballon, Jacob S.; Bartels, Matthew N.; Kimhy, David (Frontiers in Psychiatry, 2018)
Background: Hypomanic episodes are characterized by increased goal-directed behavior and psychomotor agitation. While the affective, cognitive, and behavioral manifestations of such episodes are well-documented, their physiological influence on aerobic capacity and cardiopulmonary functioning are unknown. Methods: We describe a case report of an individual with schizophrenia who experienced a hypomanic episode while serving as a control participant (wait list) in a single-blind, randomized clinical trial examining the impact of aerobic exercise (AE) on neurocognition in people schizophrenia. As part of the trial, participants completed two scheduled clinical assessments and cardiopulmonary exercise tests (VO2max) at baseline and 12 weeks later at end of study. All participants received standard psychiatric care during the trial. Following a baseline assessment in which he displayed no evidence of mood lability, the subject returned on Week-12 for his scheduled follow-up assessment displaying symptoms of hypomania. He was able to complete the follow-up assessment, as well as third assessment 2 weeks later (Week-14) when his hypomanic symptoms ebbed. Results: While not engaging in AE, the subject's aerobic capacity, as indexed by VO2max, increased by 33% from baseline to Week-12. In comparison, participants engaged in the aerobic exercise training increased their aerobic capacity on average by 18%. In contrast, participants in the control group displayed a small decline (−0.5%) in their VO2max scores. Moreover, the subject's aerobic capacity increased even further by Week-14 (49% increase from baseline), despite the ebbing of his hypomania symptoms at that time. These changes were accompanied by increases in markers of aerobic fitness including peak heart rate, respiratory exchange rate, peak minute ventilation, watts, and peak systolic blood pressure. Resting systolic and diastolic blood pressure, and peak diastolic blood pressure remained unchanged. Conclusions: Our findings suggest that hypomania produce substantial increase in aerobic capacity and that such elevations may remain sustained following the ebbing of hypomanic symptoms. Such elevations may be attributed to increased mobility and goal-directed behavior associated with hypomania, as individuals in hypomanic states may ambulate more frequently, for longer duration, and/or at higher intensity. Our results provide a first and unique view into the impact of hypomania on aerobic capacity and cardiopulmonary functioning.